ESTIMATION OF ECONOMIC INFORMATION - Витвицький, Ярослав Степанович; Витвицька, Оксана Миколаївна; Балашова, Н. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The role of information is rotined in functioning of enterprises in modern terms. Definiciyu of informative capital is given and he is selected characteristic signs. Classification of types of economic information is carried out from the point of view the estimation of its cost. The methodical going is considered near the estimation of economic information which is offered to the users as informative services. For the estimation of economic information which is used in a management an enterprise, methodical approach is offered on the basis of conception of economic values.